2012
DOI: 10.1111/j.1095-8649.2012.03252.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the biology, fisheries and conservation of the whale shark Rhincodon typus

Abstract: Although the whale shark Rhincodon typus is the largest extant fish, it was not described until 1828 and by 1986 there were only 320 records of this species. Since then, growth in tourism and marine recreation globally has lead to a significant increase in the number of sightings and several areas with annual occurrences have been identified, spurring a surge of research on the species. Simultaneously, there was a great expansion in targeted R. typus fisheries to supply the Asian restaurant trade, as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
215
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(226 citation statements)
references
References 153 publications
(284 reference statements)
8
215
2
1
Order By: Relevance
“…Results of whale shark stomach content and FA analyses presented here have shown that whale sharks feed on a variety of zooplankton prey, which is also supported by observational evidence (see Rowat & Brooks 2012). The reliance of this large predator on different prey groups means that no single matching prey FA profile exists.…”
Section: Need For a Diverse Diet For A Large Warm-water Filter Feedersupporting
confidence: 48%
“…Results of whale shark stomach content and FA analyses presented here have shown that whale sharks feed on a variety of zooplankton prey, which is also supported by observational evidence (see Rowat & Brooks 2012). The reliance of this large predator on different prey groups means that no single matching prey FA profile exists.…”
Section: Need For a Diverse Diet For A Large Warm-water Filter Feedersupporting
confidence: 48%
“…Researchers used boats and swimmers of known lengths to estimate the size of the animals. Given the longitudinal nature of the dataset and variability in size estimates from multiple researchers, we discarded intra-and inter-seasonal size estimates that differed by >2.5 m for individual whale sharks (n = 44), based on maximum growth estimates (Rowat and Brooks, 2012). To ensure this did not discard larger sharks only, we tested the relationship between visual estimate differences (2-10 m) and mean L T and found it to be not significant (r 2 = 0.038, p > 0.05).…”
Section: Size Estimatesmentioning
confidence: 99%
“…The largest of the shark species, whale sharks are highly mobile (e.g., Wilson et al, 2006;Sleeman et al, 2010;Berumen et al, 2014;Robinson et al, 2017), but form predictable seasonal aggregations in hotspots around the world, predominantly associated with the presence of food (e.g., Motta et al, 2010;Robinson et al, 2013;Rohner et al, 2015a). Some whale sharks display a degree of site fidelity on an annual and inter-annual basis (Graham and Roberts, 2007;Holmberg et al, 2008;Fox et al, 2013;Araujo et al, 2017), and this predictability makes the whale shark an ideal target species for wildlife tourism (Catlin and Jones, 2010;Rowat and Brooks, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whale sharks are known to move large distances [20] and their movements or presence at some sites have been linked with oceanographic features [20,21]. However, true migration, implying the movement away from a location over a long distance and a subsequent return, has not been registered to date [22], although photo identification studies have shown that individuals persist at sites over extended periods [23].…”
Section: Introductionmentioning
confidence: 99%